Hereditary breast cancer and ovarian cancer: clinical course and treatment - V. V. Semiglazov; A. Е. Protasova; G. K. Kalikeev (ABV-press, 2021)
This article analyzes current problems associated with surgical and systemic treatment for hereditary breast and ovarian cancers (including those associated with BRCA1/2 gene mutations). We discuss the issues related to clinical course of multiple primary tumors and their sensitivity to cytostatic and targeted therapy.